Comparative analysis of data wiping technique for android using EXT4 file system - Mat Noh, Nurhanisah; Mohamad, Kamaruddin Malik (Penerbit UTHM, 2017)
Data wiping is a useful technique which can prevent possible data recovery in a file system [1]. All the data in the file system will be permanently deleted by using this technique. In a forensics field, data wiping is so important because it can avoid risking sensitive data falling into the wrong hands [2]. The key of data wiping is to overwrite original data with garbage data. Once the garbage data replaced the original data, all the information will lose forever. Mobile devices such as cellphone or smartphone have become a part of people’s daily lives. They are exposed to facilitating criminal activity or otherwise being involved when crimes occur [3]. Although, these mobile devices can contain personal information including call history, text messages, e-mails, images memos, contacts, and many more. These devices can be used to communicate, exchange image, connect to social networks, blog, take notes, record video and audio and much more .So, many information that we have in our mobile devices. Sometimes, certain important information we want to delete to avoid other people read it. But, most of the people that use smartphone did not know that the data still keep in the phone. By using data wiping the data or information will permanently delete. In July 2014, Avast (a famous security software vendor) claimed that they recovered an abundance of personal data from 20 used smartphones [1]. In order to prevent the possible recovery of sensitive data, it is necessary to clean files by a data wiping.